HIV, sexually transmitted infections, and risk behaviours in male sex workers in London over a 10 year period. Issue 5 (17th August 2006) - Sethi, G; Holden, B M; Gaffney, J; Greene, L; Ghani, A C; Ward, H
Abstract : Objectives: To describe changing characteristics of men who sold sex in London between 1994 and 2003. Methods: A baseline survey of 823 male sex workers attending a specialist clinic, plus follow up of 628 men for 1379 person years. Results: Men recruited earlier (1994 to 1996) were more likely than those recruited later (2000 to 2003) to be UK born and to self define as homosexual. Later recruits included more men from South/Central America and eastern Europe and a higher proportion reported regular female partners. Baseline prevalence of HIV was 9% (59/636), and multivariate analysis showed an associated with injecting drug use and unprotected sex with a casual partner. During follow up there were 49 incident cases of HIV. Survival analysis showed earlier recruitment (1994–6) to be associated with a higher incidence of HIV. The prevalence of gonorrhoea increased over time. Conclusions: Men who sell sex are at risk of HIV and other STIs, but these risks do not appear to be directly linked to sex work. The changing demographics of these men is associated with different patterns of infection and poses challenges for service delivery.